Blanket-like Bi2MoO6 coated on TiO2 NTA: Solvothermal construction and the enhanced photocatalytic hydrogen generation performance. Issue 16 (15th August 2021) - Hou, Junwei; Lu, Yuan; Xu, Xiaoling; Kong, Lingcong; Liu, Yansheng; Chen, Mengmeng; Wang, Qingyao
Abstract: Photocatalytic water splitting for hydrogen production was recognized as an effective strategy to obtain renewable energy for solving the environmental pollution and resource shortage crisis. Herein, we explored the solvothermal deposition method to successfully prepare blanket-like Bi2 MoO6 coated on TiO2 nanotube arrays (TiO2 NTA/Bi2 MoO6 ), and the TiO2 NTA/Bi2 MoO6 photocatalyst showed outstanding visible light-driven photocatalytic water splitting capacity, and the hydrogen evolution rate achieved 129.26 μmol h -1  cm -2 . Moreover, the sample also exhibited high photocatalytic pollutant decomposition performance. The remarkable photocatalytic performance was attributed to the synergistic effect of Bi2 MoO6 and TiO2 NTA in the matched energy band location for solar absorption and carrier transportation. The synthesis and photocatalytic water splitting of Bi2 MoO6 /TiO2 NTA could afford the reproducible lesson for novel resource utilization of semiconductor photocatalysts.